Macroeconomics : principles and tools - O'Sullivan, Arthur; Sheffrin, Steven M. (Upper Saddle River, N.J. : Prentice Hall, 2003)
For one-semester, freshman/sophomore level courses in "Principles of Macroeconomics", this text has a strong foundation in demand and supply, the most important topic in learning and teaching principles of economics.
I. INTRODUCTION AND KEY PRINCIPLES. 1. Introduction: What Is Economics? 2. Key Principles of Economics. 3. Markets in the Global Economy. 4. Supply, Demand, and Market Equilibrium. II. THE BASIC CONCEPTS IN MACROECONOMICS. 5. Measuring a Nation's Production and Income. 6. Unemployment and Inflation. III. THE ECONOMY IN THE LONG RUN. 7. Classical Economics: The Economy at Full Employment. 8. Why Do Economies Grow? IV. ECONOMIC FLUCTUATIONS. 9. Aggregate Demand and Aggregate Supply. 10. Keynesian Economics and Fiscal Policy. 11. Investment and Financial Intermediation. V. MONEY, BANKING, AND MONETARY POLICY. 12. Money, the Banking System, and the Federal Reserve. 13. Monetary Policy in the Short Run. VI. INFLATION, UNEMPLOYMENT, AND ECONOMIC POLICY. 14. From the Short Run to the Long Run. 15. The Dynamics of Inflation and Unemployment. 16. Current Issues in Macroeconomic Policy. VII. THE INTERNATIONAL ECONOMY. 17. International Trade and Public Policy. 18. The World of International Finance.
A variety of multi-media instructional tools, including a web site, is available to supplement the text.
Includes bibliographical references and index.
Keywords: Macroeconomics